The modification of a computer simulation for use in the professional training of South African secondary school teachers with specific reference to the probationary year - Marsh, Cecille Joan Anna (Rhodes University, Faculty of Education, Department of Education, 1989)
The topic of this thesis arose out of a desire to meet the need for a practical means of supplementing the preparation of Higher Diploma of Education (H.D.E.) students for their future role as first-year teachers. It was established that this need was not adequately filled by conventional university teacher-training methods. The literature about computerised simulation of role-playing and teaching activities was investigated and the investigation indicated that such simulations had been relatively successful. A published American computer simulation, TENURE, in which the student plays the role of a first-year teacher, was selected for modification to meet the needs of South African students. This program is implemented in the TUTOR computer language and runs on the Control Data South Africa PLATO system. In order to determine the needs of South African students, two groups of Rhodes University students worked through the simulation as it was being modified. The modifications were adapted according to the students' responses to a questionnaire. The simulation has been tested by 72 H.D.E. students and several educationists and the response has been positive
Keywords: Computer simulations; High school teachers; Teacher training